Treatment with edoxaban attenuates acute stroke severity in mice by reducing blood-brain barrier damage and inflammation - Bieber, Michael; Foerster, Kathrin; Haefeli, Walter E.; Pham, Mirko; Schuhmann, Michael K.; Kraft, Peter (International journal of molecular sciences, 2021)
Patients with atrial fibrillation and previous ischemic stroke (IS) are at increased risk of cerebrovascular events despite anticoagulation. In these patients, treatment with non-vitamin K oral anticoagulants (NOAC) such as edoxaban reduced the probability and severity of further IS without increasing the risk of major bleeding. However, the detailed protective mechanism of edoxaban has not yet been investigated in a model of ischemia/reperfusion injury. Therefore, in the current study we aimed to assess in a clinically relevant setting whether treatment with edoxaban attenuates stroke severity, and whether edoxaban has an impact on the local cerebral inflammatory response and blood-brain barrier (BBB) function after experimental IS in mice. Focal cerebral ischemia was induced by transient middle cerebral artery occlusion in male mice receiving edoxaban, phenprocoumon or vehicle. Infarct volumes, functional outcome and the occurrence of intracerebral hemorrhage were assessed. BBB damage and the extent of local inflammatory response were determined. Treatment with edoxaban significantly reduced infarct volumes and improved neurological outcome and BBB function on day 1 and attenuated brain tissue inflammation. In summary, our study provides evidence that edoxaban might exert its protective effect in human IS by modulating different key steps of IS pathophysiology, but further studies are warranted.